A Study of Coronary Heart Patients’ Lifestyle at Zainoel Abidin Hospital, Banda Aceh, Indonesia (Bangladesh Journal of Medical Science, 2023)
Background: About 40% of heart disease patients do not realize they have coronary heart disease (CHD). Based on the lifestyle of people in Aceh, several factors can increase the CHD risk, such as smoking, coffee, fatty foods, stress, and lack of physical activity. Such a lifestyle has the potential to increase the risk of CHD, as evidenced by statistical papers reporting high levels of CHD cases in Aceh. This study was aimed to review the patients’ lifestyle with coronary heart disease at Zainoel Abidin Hospital, Banda Aceh, Indonesia.Method: This research is quantitative, with a case-control design. In April 2017, 206 cases of CHD and 206 non-PJK cases were analyzed, using the patient’s medical record and a lifestyle questionnaire, in Zainoel Abidin Hospital. The result of bivariate analysis through a chi-square test showed that lifestyle factors related to CHD included diet, physical activity, smoking, coffee, and stress control (p